(untitled) (Atlas Journal of Biology, 2020)
Soil microorganisms are a fundamental part of biogeochemical cycling of nitrogen. Denitrification is an important component of nitrogen cycling, in which some microorganisms (e.g. denitrifying bacteria) use nitrate or nitrite as alternative electron acceptors. In fact, several studies have focused on various aspects of nitrogen cycling. Philippot et al. (2009) linked the distribution of the fraction of bacteria with the genetic capacity to reduce N2O to N2 to areas with low potential N2O emissions in a pasture. In addition, it was shown that a map of denitrification activity across a whole farm was reflected by maps displaying the community size and structure of a specific fraction of the denitrifyers at the site (Enwall et al., 2010). Since denitrification releases mineralized nitrogen in the soil ecosystem to the atmosphere, the balance between denitrification and N-fixation can determine the biologically available nitrogen for soils. Denitrification could be affected by soil ecosystem contaminants such as crude oil and brine as they may alter the abundance and species composition of denitrifying bacteria in predictable ways. For example, γ-Proteobacteria are known to increase in crude-oil contaminated sites and in fact, a wide diversity of γ-Proteobacteria including Pseudomonas and Vibrio species were shown to degrade hydrocarbons under nitrate reducing (NR) conditions (Rockne et al., 2000). Other studies showed that strains for several genera of γ-Proteobacteria have the ability to denitrify. In fact, it was shown that nitrate and nitrite reduction rates were increasingly inhibited at increasing NaCl concentrations when comparing treatment of fishery wastewaters. Bacterial diversity in brine-contaminated sites is expected to be less because of selection for salt-tolerant genera such as Bacillus and Pseudomonas.